Effects of priming and pacing strategy on oxygen-uptake kinetics and cycling performance - Bailey, S. J.; Vanhatalo, A.; Black, M. I.; DiMenna, F. J.; Jones, A. M. (International Journal of Sports Physiology and Performance, 2016)
Purpose: To assess whether combining prior "priming" exercise with an all-out pacing strategy is more effective at improving oxygen-uptake (VO2) kinetics and cycling performance than either intervention administered independently.